Cooperative Trading Mechanism and Satisfaction-Based Profit Distribution in a Multi-Energy Community - Wang, Jian; Xie, Ning; Ilea, Valentin; Bovo, Cristian; Xin, Hao; Wang, Yong (Frontiers in Energy Research, 2021)
With the development of distributed generation and demand-side response, traditional consumers are now converted into prosumers that can actively produce and consume electricity. Moreover, with the help of energy integration technique, prosumers are encouraged to form a multi-energy community (MEC), which can increase their social welfare through inside multi-energy sharing. This paper proposes a day-ahead cooperative trading mechanism in a MEC that depends on an energy hub (EH) to couple electricity, natural gas, and heat for all prosumers. The model of the traditional uncooperative local integrated energy system (ULIES) is also built as a comparison. A satisfaction-based profit distribution mechanism is set according to prosumers’ feelings about the extra cost they save or extra profit they gain in MEC compared with that in ULIES. Finally, case studies are set to analyze the utility of MEC in enlarging social welfare, after considering the effects of prosumers’ electricity usage patterns and buy-and-sell prices in retail market. The results of satisfaction-based profit distribution are also analyzed to verify that it can save the cost or increase the profit of each prosumer and EH.